DEVELOPMENT OF PHYSICAL QUALITIES OF PRESCHOOL CHILDREN (American Journal of Interdisciplinary Research and Development, 2022)
All the foundations of health are laid in two periods: intrauterine and preschool, and psychological and physiological. The issue of physical development of preschoolers is quite acute nowadays and worries most parents. Although sports have become fashionable in the modern world, and many follow proper nutrition, carefully take care of their health.